Mapping Acute Coronary Syndrome Registries to SNOMED CT - Sulaiman, Ismat Mohd; Karlsson, Daniel; Koch, Sabine (Methods of Information in Medicine, 2017)
Background: Malaysia and Sweden have mapped their acute coronary syndrome registries using SNOMED CT. Since similar-purposed patient registries can be expected to collect similar data, these data should be mapped to the same SNOMED CT codes despite the different languages used. Previous studies have however shown variations in mapping between different mappers but the reasons behind these variations and the influence of different mapping approaches are still unknown.Objectives: To analyze similar-purposed registries and their registry-to-SNOMED CT maps, using two national acute coronary syndrome registries as examples, to understand the reasons for mapping similarities and differences as well as their implications.Methods: The Malaysian National Cardiovascular Disease - Acute Coronary Syndrome (NCVD- ACS) registry was compared to the Swedish Register of Information and Knowledge about Swedish Heart Intensive Care Admissions (RIKS- HIA). The structures of NCVD-ACS and RIKS-HIA registry forms and their distributions of headings, variables and values were studied. Data items with equivalent meaning (EDIs) were paired and their mappings were categorized into match, mismatch, and non-comparable mappings. Reasons for match, mismatch and non-comparability of each paired EDI were seen as factors that contributed to the similarities and differences between the maps.Results: The registries and their respective maps share a similar distribution pattern regarding the number of headings, variables and values. The registries shared 101 EDIs, whereof 42% (42) were mapped to SNOMED CT. 45% (19) of those SNOMED CT coded EDIs had matching codes. The matching EDIs occurred only in pre-coordi- nated SNOMED CT expressions. Mismatches occurred due to challenges arising from the mappers themselves, limitations in SNOMED CT, and complexity of the registries. Non-comparable mappings appeared due to the use of other coding systems, unmapped data items, as well as requests for new SNOMED CT concepts.Conclusions: To ensure reproducible and reusable maps, the following three actions are recommended: (i) develop a specific mapping guideline for patient registries; (ii) openly share maps; and (iii) establish collaboration between clinical research societies and the SNOMED CT community.
Keywords: SNOMED CT; reference terminology; registry; semantic interoperability; cardiology